2019
DOI: 10.3389/fphys.2019.00802
|View full text |Cite
|
Sign up to set email alerts
|

AAV9-Mediated Overexpression of TRPM4 Increases the Incidence of Stress-Induced Ventricular Arrhythmias in Mice

Abstract: Ca 2+ activated non-selective (CAN) cation channels have been described in cardiomyocytes since the advent of the patch clamp technique. It has been hypothesized that this type of ion channel contributes to the triggering of cardiac arrhythmias. TRPM4 is to date the only molecular candidate for a CAN cation channel in cardiomyocytes. Its significance for arrhythmogenesis in living animals remains, however, unclear. In this study, we have tested whether increased expression of wild-type (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Similar results were obtained in mouse as 9-phenanthrol abolished hypoxia and re-oxygenation induced early afterdepolarization in a dose-dependent manner [21]. Cardiac specific overexpression of TRPM4 in mice increased the occurrence of ectopic ventricular beats during stress conditions (evoked by heavy exercise and β-adrenergic stimulation), but not in baseline [55], which highlights the possibility that TRPM4 can indeed generate DADs in calcium overloaded cells in vivo. Similarly, TRPM4 could be involved in aldosterone-induced atrial arrhythmias in mice [56].…”
Section: Effects Of Cba On Short-term Variability Of Repolarizationsupporting
confidence: 77%
“…Similar results were obtained in mouse as 9-phenanthrol abolished hypoxia and re-oxygenation induced early afterdepolarization in a dose-dependent manner [21]. Cardiac specific overexpression of TRPM4 in mice increased the occurrence of ectopic ventricular beats during stress conditions (evoked by heavy exercise and β-adrenergic stimulation), but not in baseline [55], which highlights the possibility that TRPM4 can indeed generate DADs in calcium overloaded cells in vivo. Similarly, TRPM4 could be involved in aldosterone-induced atrial arrhythmias in mice [56].…”
Section: Effects Of Cba On Short-term Variability Of Repolarizationsupporting
confidence: 77%
“…TRPM4 gain-of-function may inactivate the sodium channels via the depolarization of the resting membrane potential, while a loss-of-function could induce a hyperpolarization of the membrane potential, leading to a reduced cellular excitability and conduction [ 42 , 69 ]. These hypotheses were partially supported by some recent in vivo studies [ 18 , 40 , 72 ]. Regarding TRPM4 loss-of-function, the invalidation of the TRPM4 gene in mice induced a multilevel conduction block without any modification of the ventricular AP characteristics [ 40 ].…”
Section: Inherited Cardiac Disorders Of Trpm4 Channelssupporting
confidence: 53%
“…As regards the TRPM4 gain-of-function, Pironet and colleagues have overexpressed wild-type TRPM4 channels in living mice via tail vein injection of AAV9 particles. The authors did not observe any increase in conduction abnormalities in mice overexpressing TRPM4 [ 72 ].…”
Section: Inherited Cardiac Disorders Of Trpm4 Channelsmentioning
confidence: 99%
“…The current study further supported the idea of the role of TRPM4 in AVB. A developed ventricular fibrillation and idioventricular rhythm had been recorded in overexpression of TRPM4 [21]. Thus, our study regards TRPM4 mutation as the result of AVB among 10 identified mutations.…”
Section: Discussionmentioning
confidence: 75%